Computational pathology, new horizons and challenges for anatomical pathology - Washington L. C. dos-Santos; Luiz A. R. de Freitas; Angelo A. Duarte; Michele F. Angelo; Luciano R. Oliveira (BMC, 2022)
Abstract The emergence of digital pathology environments and the application of computer vision to the analysis of histological sections has given rise to a new area of Anatomical Pathology, termed Computational Pathology. Advances in Computational Pathology may substantially change the routine of Anatomical Pathology laboratories and the work profile of the pathologist.